THE EFFECT OF EXPERIENCE AUDIT, AUDITOR’S PROFESSIONALISM AND OBEDIENCE PRESSURE ON AUDIT JUDGMENT WITH TASK COMPLEXITY AS MODERATION (STUDY ON BPK RI RIAU PROVINCE REPRESENTATIVE) - Miftarahma Miftarahma; Amir Hasan; Andreas Andreas (Program Studi Pendidikan Ekonomi Universitas Riau, 2018)
The objective of this study is to investigate the effect of Experience Audit, Auditor’sProfessionalism and obedience pressure on audit judgment with task complexity asmoderation. The population are auditors on BPK RI Riau Province Representative.Total sampling was used as sampling method, it was obtained 54 auditors assamples. Statical method used to test research hypothesis is using moderatedregression analysis (MRA). The result showed experience audit did not effect onaudit judgment, while auditor’s professionalism have effect on audit judgment andobedience pressure have effect on audit judgment, also found that task complexitydoes not moderates the effect of experience audit on audit judgment, while taskcomplexity moderates the effect of Auditor’s Professionalism on audit judgment andtask complexity moderates the effect of Obedience Pressure on Audit Judgment.